The Information Economy and the Labor Theory of Value. Issue 1 (2nd January 2017) - Fuchs, Christian
Abstract: This article discusses aspects of the labor theory of value in the context of the information industries. First, taking the Temporal Single-System Interpretation (TSSI) of Marx's labor theory of value as methodology, the article calculates economic demographics at the level of socially necessary labor time and prices of an example case. Second, the article questions the assumption that the labor theory of value cannot be applied to the information industries. This article tests this hypothesis with an analysis of the development of labor productivity in six countries. The article concludes that the labor theory of value is an important tool for understanding the information economy and the peculiarities of the information commodity.